Non-linearity, complexity, and quantization concepts in biology - Theise, Neil D.; Tuszynski, Jack A. (Frontiers in Human Neuroscience, 2026)
Founders of quantum mechanics (QM) anticipated that revisions to classical physics due to strange elements of quantum reality, would necessitate similar changes in biology. Complexity theory, systems biology and quantum biology provide possible solutions indicating that subject/object separation is a useful fiction for reductive science. Direct correlates to such QM observational/measurement issues as Complementarity and Uncertainty may justify the introduction of an analog of Heisenberg's uncertainty and the Planck constant for living systems. The phase space of “adjacent possibles” for biological systems from which one “actual” is selected resembles the collapse of the QM wave function. Since biological systems are hierarchical, this occurs across organizational scales resulting in biological coherence. The location of a quantum/classical boundary is unclear due to complexity. Whether biological systems' characteristics arise directly from QM or are of a different origin remains unsettled. To combine non-linear with quantum properties across biological scales we propose the Method of Coherent Structures (MCS), developed for quantum many-body systems. In MCS, a higher-level scale provides a classical envelope for quantum fluctuations at the lower scale. It yields a seamless transition from non-linear classical fields to quantum excitations and accounts for the emergence of complexity by incorporating metabolic energy supply.